Loneliness and aging - Santos, Ana Maria Ribeiro dos; Marques, Maria do Céu Mendes Pinto (Revista de Enfermagem da UFPI, 2024)
Scientific evidence on loneliness shows that this feeling can act as a decisive negative factor in maintaining health. In this sense, an editorial on the subject stated that the damage to health is clear and associated loneliness with an increased risk of cardiovascular diseases, hypertension, diabetes, infectious diseases, impaired cognitive function, depression and anxiety. The editorial also highlighted that this is an issue that requires society’s attention and, as a result, a committee was created to study loneliness and social isolation.(1) Due to the evidence of the harm it can cause or worsen, loneliness has become one of the major health concerns in the 21st century. As a result, initiatives have been developed and the governments of the United Kingdom and Japan created Ministries of Loneliness in 2018 and 2021, respectively.(2) Also, a health authority in the United States showed the consequences of insufficient connection for physical health and highlighted a 29% higher risk of heart disease, a 32% higher occurrence of stroke and a 50% higher chance of developing dementia in older people. In addition, it estimated that the lack of social connection increases the risk of premature death by more than 60%.(3) . . .